Thermodynamic Stability of the Non-Native α-Helical Intermediates of β-Lactoglobulin by Conjugation with Three Different Kinds of Carboxymethyl Cyclodextrins - Chamani, J. (Asian Journal of Chemistry, 2010)
β-LactoglobuIin-carboxymethyl cyclodextrin conjugates were prepared by using water soluble carbodiimide. Three kinds of carboxymethyl cyclodextrins (CM-CyDs) differing in molecular mass were used to investigate the effects of different CM-CyD contents and hydrophobicity on the structural changes in β-lactoglobuIin (β-LG). The effect of CM-CyDs on the structure of β-LG was utilized to investigate the contribution of hydrophobic interactions to the stability of the protein. It is generally assumed that folding intermediates contain partially formed native-like secondary structures. However, on considering the fact that the conformational stability of the intermediate state is simpler than that of the native state, it would be expected that the secondary structures in a folding intermediate would not necessarily be similar to those of the native state. β-LG is a predominantly β-sheet protein, although it has a markedly high intrinsic preference for α-helical structure. The formation of non-native α-helical intermediate of β-LG was conjugated by CM-CyDs including CM-α-CyD, CM-β-CyD and CM-γ-CyD as special condition. The m values of the intermediate state of β-LG by CM-CyDs showed substantial variation. The enhancement of m values as the stability criterion of non-native α-helical intermediate state corresponded with increasing glucose units of the cited CM-CyDs. The present results suggest that the folding reaction of β-LG follows a non-hierarchical mechanism and hydrophobic interactions play important roles in stabilizing the non-native α-helical intermediate state.